2019
DOI: 10.5430/jnep.v9n8p99
|View full text |Cite
|
Sign up to set email alerts
|

Nurse managers’ self-evaluations of their management competencies and factors associated with their ability to develop staff

Abstract: The purpose of this study was to clarify how Japanese nurse managers (i.e., “shunin”) or higher-ranked positions self-rate their nursing management competencies and to identify factors associated with their ability to develop staff. Data were collected using a questionnaire based on the 41-item Management Index for Nurses. This index assesses the competencies related to six components of nursing management: planning, motivating staff, developing staff, communication, organization, and ensuring safety. The tota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Nurse managers play a critical role in creating a positive work environment for nurses to ensure the delivery of safe and high‐quality nursing care, which facilitates the attainment of organisational goals and outcomes (McSherry et al, 2012). To fulfil this role, nurse managers require effective leadership skills to actively engage in dealing with staff nurses, peers and top administrators (McSherry et al, 2012; Shomura, Okabe, Tejima, Yaguchi, Iwamoto, & Sakurai, 2019). In particular, the current health care climate is characterized by increased complexity, shortages in nursing staff, budget cuts, rising costs and increasing patient acuity.…”
Section: Introductionmentioning
confidence: 99%
“…Nurse managers play a critical role in creating a positive work environment for nurses to ensure the delivery of safe and high‐quality nursing care, which facilitates the attainment of organisational goals and outcomes (McSherry et al, 2012). To fulfil this role, nurse managers require effective leadership skills to actively engage in dealing with staff nurses, peers and top administrators (McSherry et al, 2012; Shomura, Okabe, Tejima, Yaguchi, Iwamoto, & Sakurai, 2019). In particular, the current health care climate is characterized by increased complexity, shortages in nursing staff, budget cuts, rising costs and increasing patient acuity.…”
Section: Introductionmentioning
confidence: 99%
“…These challenges called for changes such as the development of new systems and protocols of care, and new ways of working, which were mostly coordinated by nurse managers [ 38 ]. Their role in sustaining the quality of care was rated the most important in past studies, involving personal mastery such as their abilities to handle contingencies and projecting a sense of confidence, calm, control, and security during crises [ 39 , 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…With further validation, it could be adopted as a tool to assess the competencies of nurse managers against standards of performance [ 47 ]. Regarding the training of nurse managers, previous studies have indicated that a one-off education program failed to improve the competencies of nurse managers [ 37 ], and many scholars have stressed the importance of providing systematic and continuous training to nurse managers [ 41 , 48 ]. The findings of this study can serve as a basis for designing these training programmes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation